PAI LEARNING MANAGEMENT IN INSTILLING RELIGIOUS MODERATION VALUES IN HIGH SCHOOL - Junaidah Junaidah; Mayang Sari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
SMAS Taman Siswa Teluk Betung in Bandar Lampung has various types of students and various religions. SMAS Taman Siswa Teluk Betung is a plural school and indirectly they have religious tolerance. The aim of this study was to describe PAI learning management in instilling the value of religious moderation at SMAS Taman Siswa Telukbetung Bandar Lampung. This was case study research which was qualitative research that sought to find meaning, investigate processes, and gain in-depth understanding. This study found that PAI learning planning at Taman Siswa High School aimed to form good morals through psychomotor, cognitive and affective assessments with the values of religious moderation. Learning strategies included methods, techniques and media to facilitate student understanding and retain information from the teacher. The implementation of learning consisted of preliminary, core and closing activities. The introduction began with greetings and Lampung culture. Implementation of religious moderation values was carried out in PAI's core activities, such as group discussions and presentations. The closing activity was carried out by providing examples and guidance to students in applying the values of religious moderation in everyday life. Learning evaluation involved ongoing formative and summative assessment at the end of learning. The output of SMAS Taman Siswa was students who had good personalities, commendable morals, obey the rules, and prioritize values such as where the earth is stepped, there the sky is upheld. This research contributed to PAI learning management, especially to the value of religious moderation in high school.